Cost of microbial larviciding for malaria control in rural Tanzania. Issue 11 (31st August 2016) - Rahman, Rifat; Lesser, Adriane; Mboera, Leonard; Kramer, Randall
Abstract: Objective: Microbial larviciding may be a potential supplement to conventional malaria vector control measures, but scant information on its relative implementation costs and effectiveness, especially in rural areas, is an impediment to expanding its uptake. We perform a costing analysis of a seasonal microbial larviciding programme in rural Tanzania. Methods: We evaluated the financial and economic costs from the perspective of the public provider of a 3‐month, community‐based larviciding intervention implemented in twelve villages in the Mvomero District of Tanzania in 2012–2013. Cost data were collected from financial reports and invoices and through discussion with programme administrators. Sensitivity analysis explored the robustness of our results to varying key parameters. Results: Over the 2‐year study period, approximately 6873 breeding sites were treated with larvicide. The average annual economic costs of the larviciding intervention in rural Tanzania are estimated at 2014 US$ 1.44 per person protected per year (pppy), US$ 6.18 per household and US$ 4481.88 per village, with the larvicide and staffing accounting for 14% and 58% of total costs, respectively. Conclusions: We found the costs pppy of implementing a seasonal larviciding programme in rural Tanzania to be comparable to the costs of other larviciding programmes in urban Tanzania and rural Kenya. Further research should evaluate the cost‐effectiveness of larviciding relative to, and in combination with, other vector control strategies in rural settings.